1995
DOI: 10.1017/s0924270800037546
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of seasonal affective disorder (SAD) in The Netherlands

Abstract: Since the description of SAD the prevalence of this disorder has been of particular interest. The more so, because early studies, indicated the correctness of the on theoretical grounds - expected interaction between latitude and prevalence rate of SAD. More eleborate prevalence studies, mainly in the USA indeed showed a positive correlation between prevalence rate and latitude. In Europe, only few studies have appeared. Although the results of most of these studies are preliminary and research-methods and cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The baseline tests (T1) were conducted between April and June, which makes that the second series of tests (T2) were conducted in the autumn and the beginning of the winter (October–December). This period of the year is characterised by rain and cold weather and seasonal changes in mood and behavior, a phenomenon also experienced across the healthy population (Mersch et al, 1999). The season could have had an impact on the results of the maximal exercise test, especially in the CG.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline tests (T1) were conducted between April and June, which makes that the second series of tests (T2) were conducted in the autumn and the beginning of the winter (October–December). This period of the year is characterised by rain and cold weather and seasonal changes in mood and behavior, a phenomenon also experienced across the healthy population (Mersch et al, 1999). The season could have had an impact on the results of the maximal exercise test, especially in the CG.…”
Section: Discussionmentioning
confidence: 99%
“…There are at least 6 reliability studies (97±102) and 12 validity studies ( (12,21,77,93). There are at least 6 reliability studies (97±102) and 12 validity studies ( (12,21,77,93).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Most studies include an SS of 11 or greater as one of the criteria for SAD, thus 11 seems to be the standard (14,15,18,19,21,23,77,78,85,86,90,93,94,106). Most studies include an SS of 11 or greater as one of the criteria for SAD, thus 11 seems to be the standard (14,15,18,19,21,23,77,78,85,86,90,93,94,106).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least 6 reliability studies (97±102) and 12 validity studies ( (102). There are two main types of validation studies of the SPAQ: ®rst, studies that have found signi®cantly different mean depression ratings scores (or SPAQ scores) between groups of SAD patients and normal individuals (9,14,15,93,97,98); and secondly, studies that compare SPAQ diagnoses with clinical diagnoses of SAD (12,21,77,93,104,105). One study found excellent agreement (77) while the others found only moderate agreement.…”
Section: Methodological Issuesmentioning
confidence: 99%